Perancangan Sistem Informasi Rekam Medis Elektronik Berbasis Website Menggunakan Metode User-Centered Design (Studi Kasus: Rumah Sakit Universitas Mataram) - Khairunnisa Fitriani; Santi Ika Murpratiwi; Moh. Ali Albar (Journal of Computer Science and Informatics Engineering (J-Cosine), 2026)
The growing demand for integrated and secure medical documentation has driven hospitals to adopt Electronic Medical Record (EMR) systems. This study focuses on the design of a web-based EMR system for the University of Mataram Hospital using the User-Centered Design (UCD) approach. The design aims to overcome the limitations of existing systems, particularly those related to hospital workflows that hinder usability and adaptability. The EMR module is envisioned as part of a microservice-based Hospital Information System, integrating key functionalities such as patient data management, medical history tracking, referral and control letter generation, and dashboard summaries. The development process includes user analysis, UML modeling, and UI/UX prototyping. The resulting prototype is evaluated using the User Experience Questionnaire (UEQ) with direct feedback from hospital staff. The final system is expected to be better aligned with the operational workflows of University of Mataram Hospital, offering improved integration, usability, and adaptability compared to the previous system.